2014
DOI: 10.1093/molbev/msu210
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Genetic Survey Provides Insights into the Captive Management and Reintroduction of Giant Pandas

Abstract: The captive genetic management of threatened species strives to preserve genetic diversity and avoid inbreeding to ensure populations remain available, healthy, and viable for future reintroduction. Determining and responding to the genetic status of captive populations is therefore paramount to these programs. Here, we genotyped 19 microsatellite loci for 240 captive giant pandas (Ailuropoda melanoleuca) (∼64% of the captive population) from four breeding centers, Wolong (WL), Chengdu (CD), Louguantai (LGT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Reintroduction refers to the intentional movement of captive‐born organisms into, or near, the species’ natural historic range to reestablish or augment a wild population (Beck, Rapaport, Price, & Wilson, ). Many reintroduction programs involving endangered or vulnerable species have been carried out for conservation purposes worldwide, such as that of black bears, Ursus americanu , (Clark, Huber, & Servheen, ), Mexican wolves, Canis lupus baileyi , (Oakleaf, Stark, Overy, & Smith, ), and giant pandas, Ailuropoda melanoleuca , (Shan et al, ; Yang et al, ). However, the average success rate of reintroduction is estimated to be between 26% and 32% from 2002 to 2014 (Fischer & Lindenmayer, ; Jule, Leaver, & Lea, ), which suggests that the technique of reintroductions needs further investigation and improvement in order to ensure that they are viable options (Fischer & Lindenmayer, ; Seddon, Strauss, & Innes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reintroduction refers to the intentional movement of captive‐born organisms into, or near, the species’ natural historic range to reestablish or augment a wild population (Beck, Rapaport, Price, & Wilson, ). Many reintroduction programs involving endangered or vulnerable species have been carried out for conservation purposes worldwide, such as that of black bears, Ursus americanu , (Clark, Huber, & Servheen, ), Mexican wolves, Canis lupus baileyi , (Oakleaf, Stark, Overy, & Smith, ), and giant pandas, Ailuropoda melanoleuca , (Shan et al, ; Yang et al, ). However, the average success rate of reintroduction is estimated to be between 26% and 32% from 2002 to 2014 (Fischer & Lindenmayer, ; Jule, Leaver, & Lea, ), which suggests that the technique of reintroductions needs further investigation and improvement in order to ensure that they are viable options (Fischer & Lindenmayer, ; Seddon, Strauss, & Innes, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Rwanda’s Virunga Massif, close monitoring of individual animals – facilitating the detection and treatment of medical conditions – has led to an annual 4.1%±0.09% increase in the number of mountain gorillas ( Gorilla beringei beringei ) in groups habituated to human observation, versus an annual 0.7%±0.06% decline in the number of unhabituated conspecifics 7 . Proactive captive-breeding of giant pandas, meanwhile, has resulted in the birth of numerous offspring through artificial insemination, producing offspring both for exhibition in zoos and for introduction to the wild – effectively reversing the decline of a conservation flagship species 8 . Though direct intervention may be necessary for the effective conservation of wildlife, unintended effects may ultimately harm populations.…”
mentioning
confidence: 99%
“…Despite correcting the identified parentage errors in the Attwater's prairie‐chicken pedigree prior to the 2013 breeding season, a total of 11 proposed pedigree‐based breeding pairs (29%) still possessed r DNA ≥0.125. This suggested that we did not correct all of the parentage errors in the pedigree or that other factors such as assuming the original founders were unrelated may be incorrect (Shan et al ., ). The benefit of knowing founder relationships for mean kinship breeding strategies for minimizing inbreeding, however, decreases over time (<5 generations) depending on the size of the founding population and reproduction rate (Rudnick & Lacy, ).…”
Section: Discussionmentioning
confidence: 97%